Superconducting Quantum Oscillations and Anomalous Negative Magnetoresistance in a Honeycomb Nanopatterned Oxide Interface Superconductor - Yishuai Wang; Siyuan Hong; Wenze Pan; Yi Zhou; Yanwu Xie (Physical Review X)
The extremely low superfluid density and unprecedented tunability of oxide interface superconductors provide an ideal platform for studying fluctuations in two-dimensional superconductors. In this work, we fabricate an LaAlO_{3}/KTaO_{3} interface superconductor patterned with a nanohoneycomb array of insulating islands. Little-Parks-like magnetoresistance oscillations are observed, which are dictated by the superconducting flux quantum h/2e. Moreover, an anomalous negative magnetoresistance (ANMR) appears under a weak magnetic field, suggesting magnetic-field-enhanced superconductivity. By examining their dependences on temperature, measurement current, and electrical gating, we conclude that both phenomena are associated with superconducting order parameter: The h/2e oscillations provide direct evidence of Cooper-pair transport, and the ANMR is interpreted as a consequence of multiple connected narrow superconducting paths with strong fluctuations.